4f crystal field ground state of the strongly correlated topological insulator SmB6 - Sundermann, Martin; Haverkort, Maurits W. (Physical review letters, 2018)
We investigated the crystal-electric field ground state of the 4f manifold in the strongly correlated topological insulator SmB6 using core-level nonresonant inelastic x-ray scattering. The directional dependence of the scattering function that arises from higher multipole transitions establishes unambiguously that the Γ8 quartet state of the Sm f5 J=5/2 configuration governs the ground-state symmetry and, hence, the topological properties of SmB6. Our findings contradict the results of density functional calculations reported so far.